Blockchain dan Cryptocurrency: Tantangan Regulasi dan Kepastian Hukum dalam Arsitektur Keuangan Digital Indonesia - Gilang Rizki Aji Putra; Sri Ajeng Murni Cahyani Putri (BULETIN ADALAH, 2025)
Blockchain and cryptocurrency have disrupted global financial systems through decentralized and transparent transactions. In Indonesia, however, these technologies face regulatory challenges rooted in conventional legal frameworks. This article analyzes Indonesia’s regulatory landscape on blockchain and cryptocurrency, identifies key issues, and proposes reform directions. Using normative legal research with statutory and comparative approaches, the study finds three main problems: unclear dual legal status of cryptocurrency as commodity and financial asset, weak mechanisms for seizure and enforcement of digital assets, and tension between regulation and the borderless nature of blockchain. Despite reforms under the P2SK Law and OJK supervision, significant legal gaps remain. The article concludes that comprehensive digital asset legislation is urgently needed. Keywords: Blockchain, Cryptocurrency, Legal Certainty, Digital Assets, Regulation.